PENGARUH CITRA MERK, HARGA DAN LOKASI TERHADAP KEPUTUSAN BERKUNJUNG PADA QQ KTV DI KOTA SAMARINDA - Masdari, Farhan; Dwijatenaya, Ida Bagus Made Agung; Fahleti, Widya Hana (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2021)
The fluctuating number of QQ KTV visitors shows that consumers often move, compare prices, and locations with other family karaokes. This study aims to determine the effect of brand image, price, and location partially on visiting decisions, as well as to determine the effect of brand image, price and location together on visiting decisions. This research was conducted in June 2019 to June 2020 in QQ KTV Samarinda. The population is 141 visitors, using the Slovin formula and the error rate is 5%, the number of samples is 105 respondents. Then analyzed using the method of multiple linear regression analysis. The results obtained are the brand image, price, and location of each positive and significant effect partially. And brand image, price, and location have a positive and significant effect simultaneously on the decision to visit the QQ KTV in Samarinda.Keywords: brand image, price, location, visiting decision.